2017
DOI: 10.1016/j.jpba.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative LC–MS/MS method for simultaneous determination of cocaine and its metabolites in whole blood

Abstract: As new metabolic pathways of cocaine were recently identified, a high performance liquid chromatography tandem mass spectrometry (LC-MS/MS) method was developed to simultaneously determine cocaine and nine cocaine-related metabolites in whole blood samples. One-step solid phase extraction was used to extract all of the ten compounds and corresponding internal standards from blood samples. All compounds and internal standards extracted were separated on an Atlantis T3 (100Å, 3 µm, 2.1 mm × 150 mm I.D) column an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 33 publications
0
26
0
2
Order By: Relevance
“…For the interday accuracy, the values found were within the range of 1.9% (high MDMA control) to 18.6% (low aldicarb control). Chen et al reported similar accuracy values. Arora et al found values between 0.1% and 19% in the precision assay and 82.1% to 119% in the accuracy of the LC‐MS method.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…For the interday accuracy, the values found were within the range of 1.9% (high MDMA control) to 18.6% (low aldicarb control). Chen et al reported similar accuracy values. Arora et al found values between 0.1% and 19% in the precision assay and 82.1% to 119% in the accuracy of the LC‐MS method.…”
Section: Resultsmentioning
confidence: 66%
“…A significant matrix effect of blood was observed for some substances (aldicarb and bromazepam [increase of signal] and phenytoin and valproic acid [suppression]). However, they are not considered as discrepant compared with those published in the literature with similar methodologies . In addition, since the sensitivity of the method was considered satisfactory, the matrix effect did not negatively influence the application of the method.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Its TDM is necessary; it is fulfilled through the measurement of trough plasmatic concentrations14 . HPLC-UV is an accurate method but needs an extended step of extraction followed by the injection in the HPLC-UV system15 .…”
mentioning
confidence: 99%
“…As precisões intra e inter-dia foram consideradas aceitáveis Um efeito matriz relevante foi observado para algumas substâncias (aldicarbe, e bromazepam (aumento de sinal) e fenitoína (supressão). No entanto, não são considerados discrepantes comparados aos publicados na literatura com metodologias similares (CHEN et al, 2016;SEMPIO et al, 2014). Além disso, como a sensibilidade do método foi considerada satisfatória, o efeito matriz não influenciou negativamente na aplicação do método.…”
Section: Precisão Intra E Inter-ensaiounclassified